Modulating excitation/inhibition balance through transcranial electrical stimulation: physiological mechanisms in animal models - Estévez-Rodríguez, Marta; Sánchez-Garrido Campos, Guillermo; Zafra, Ángela M.; Cordones, Isabel; Márquez-Ruiz, Javier (Frontiers in Neuroscience, 2025)
The balance between excitatory and inhibitory (E/I) activity is a fundamental property of neural circuits, ensuring precise information processing and preventing pathological states such as hyperexcitability or network silencing. Disruptions in this balance have been linked to several neurological and psychiatric disorders, including epilepsy, autism, and schizophrenia. Transcranial electrical stimulation (tES) can modulate the E/I balance through mechanisms that affect synaptic plasticity, neurotransmitter systems, and network synchronization. The main tES modalities—transcranial direct current stimulation (tDCS), transcranial alternating current stimulation (tACS), and transcranial random noise stimulation (tRNS)—operate through distinct physiological principles, enabling the modulation of neuronal excitability and oscillatory dynamics. Animal models offer controlled experimental conditions to study the effects of tES on E/I regulation at the cellular, synaptic, and network levels. Preclinical research has revealed polarity-dependent plasticity with tDCS, frequency-specific entrainment with tACS, and GABAergic modulation with tRNS. These findings are essential for validating computational models and refining stimulation protocols. Future studies should integrate multimodal technologies to enhance the translational relevance of tES and develop personalized neuromodulation strategies targeting E/I imbalance in brain disorders.